Gli spazi monastici. Le dipendenze cavensi e la Basilicata medievale: alcuni casi studio (secc. XI-XIII) - Visentin, Barbara (Rivista di storia della Chiesa in Italia, 2025)
The geo-morphological, settlement and ethnic characteristics that determined the historical evolution of medieval Southern Italy made it a multifaceted territory, an osmotic area, which assimilated some of the elements of the different civilizations that had passed through it and rejected others, an ‘organism’ that was not centralized at all, at least until the rise of the Norman monarchy. In this extreme variety, the religious factor, linked above all to the monastic experience, seems to offer a particularly interesting perspective of investigation, since the monastic phenomenon is also a non-centralised organism. In particular, the lands of medieval Basilicata reveal themselves to be special places, in which the presence of monastic institutions significantly marks the evolutionary dynamics of the surrounding world.